Proceedings of the 13th Linguistic Annotation Workshop 2019
DOI: 10.18653/v1/w19-4012
|View full text |Cite
|
Sign up to set email alerts
|

An Online Annotation Assistant for Argument Schemes

Abstract: Understanding the inferential principles underpinning an argument is essential to the proper interpretation and evaluation of persuasive discourse. Argument schemes capture the conventional patterns of reasoning appealed to in persuasion. The empirical study of these patterns relies on the availability of data about the actual use of argumentation in communicative practice. Annotated corpora of argument schemes, however, are scarce, small, and unrepresentative. Aiming to address this issue, we present one step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…Experiments on the annotation of Walton schemes by annotators with a strong background in linguistics but who were provided with only the description of the schemes given in Walton, Reed, and Macagno (2008) have shown that this is an exceptionally difficult task, with results differing in both numbers of arguments annotated and the distributions of units (Lindahl, Borin, and Rouces 2019). However, recent developments in annotation guidelines for these schemes, including the decision tree-based method described in Lawrence, Visser, and Reed (2019), suggest that this situation can be improved and offer hope for the construction of scheme annotated corpora.…”
Section: Conclusion: a Is True (False)mentioning
confidence: 99%
“…Experiments on the annotation of Walton schemes by annotators with a strong background in linguistics but who were provided with only the description of the schemes given in Walton, Reed, and Macagno (2008) have shown that this is an exceptionally difficult task, with results differing in both numbers of arguments annotated and the distributions of units (Lindahl, Borin, and Rouces 2019). However, recent developments in annotation guidelines for these schemes, including the decision tree-based method described in Lawrence, Visser, and Reed (2019), suggest that this situation can be improved and offer hope for the construction of scheme annotated corpora.…”
Section: Conclusion: a Is True (False)mentioning
confidence: 99%
“…Some research adopted argumentation schemes as a framework, making comparisons with discourse relations (Cabrio et al, 2013) and collecting and leveraging data at varying degrees of granularity. At a coarse level, prior studies annotated the presence of particular argumentation schemes in text (Visser et al, 2020;Lawrence et al, 2019;Lindahl et al, 2019;Reed et al, 2008) and developed models to classify different schemes (Feng and Hirst, 2011). However, each scheme often accommodates both support and attack relations between statements, so classifying those relations requires semantically richer information within the scheme than just its presence.…”
Section: Related Workmentioning
confidence: 99%
“…Among existing datasets, the AraucariaDB corpus is the largest as far as we know and includes approximately 660 manually annotated arguments (Feng and Hirst, 2011). Lawrence et al (2019) state that annotated corpora of argumentation schemes are scarce, small, and unrepresentative. They provide an annotation tool to address the issue.…”
Section: Datasetsmentioning
confidence: 99%